Implementasi Budaya Nyadran Sebagai Sumber Belajar Etnopedagogi Di Sekolah Dasar - Mufidah, Inayatul; Widodo, Wahono; Gunansyah, Ganes (CV. Kurnia Grup, 2025)
This research is based on the importance of preserving local culture as part of national identity and character education in elementary schools. Nyadran, a Javanese cultural tradition, holds great potential as an etnopedagogical learning resource that teaches social values, spirituality, and local wisdom to students. The purpose of this study is to explore the potential of Nyadran culture as a source of learning within the educational context of elementary schools and to identify strategies for integrating it into the curriculum.This research employs a qualitative approach with an exploratory design. The subjects include teachers, students, and community figures involved with the Nyadran tradition in a specific area. Data collection was conducted through observation, in-depth interviews, and documentation of Nyadran cultural activities.The results indicate that Nyadran culture possesses educational values related to character building, spirituality, and communal harmony, which are highly relevant to instill in students. The use of this culture as a learning resource can be implemented through direct activities such as Nyadran ceremonies, recitation of prayers, and storytelling of ancestral tales presented in an engaging and contextual manner.